Macroeconomic determinants of credit risk: evidence from the Eurozone - Carvalho, P. V.; Curto, J. D.; Primor, R. (International Journal of Finance and Economics, 2022)
We propose and estimate several models controlling for firm-specific information, to examine the relation of macroeconomic variables with the probability of default of firms in the Eurozone. The novelty of our approach consists in capturing the informational value of macroeconomic factors on credit default prediction by using data from firms spanning 11 European countries; our panel data set covers 534 thousand firm-year observations. The results we obtain confirm that macroeconomic information strengthens the accuracy of models forecasting credit default of non-financial firms. With a negative effect on the probability of default, GDP growth stands out among the key macroeconomic predictors of default. Yet, we find compelling evidence that asymmetries exist within the Eurozone regarding the benign effects of GDP growth over credit risk; the reduction of the probability of default due to economic growth mostly occurs in economies more exposed to conditions of financial stress.